Real time and auto triggered facial recogition entrance system / Muhammad Raez Zahari - Zahari, Muhammad Raez (2013)
Facial recognition door entry system has recently received significant attention as another way of authenticated biometric system that ensures the security of the specified locations such as office and laboratory. Besides preventing unauthorized users, the system can keep record of people going in and out from the room. This work proposes secure entrance system utilizing face recognition technique running on low power Intel atom processor. The system will provides or delivers automated, active, real time surveillance and identification solution providing event driven alerts based on excluded status. Upon detecting any suspicious faces, the system will alert respective person incharged through connected GSM module. During the process an Intel atom motherboard will be used for interfacing between the GSM module and camera.